Ba ‘Alawi Women and The Development of Hadrami Studies in Indonesia - Husein, Fatimah (Studia Islamika, 2025)
Research concerning the Indonesian Hadrami diaspora predominantly centers on male actors, with contributions primarily from male scholars. There remains a notable lack of scholarship that adequately addresses the contributions of Hadrami female religious authorities and is authored by female scholars. I begin by examining the research surrounding the Hadrami diaspora in the Indian Ocean region. In the second part, I focus on literature concerning Hadrami women to highlight the scarcity of research that explores the dynamics of contemporary Indonesian Ba ‘Alawi female preachers, despite their impact in coloring Indonesian Islam. Finally, through the perspective of feminist epistemology and “gender jihad,” I emphasize the epistemological contributions by these preachers as the preservers and disseminators of their Sufi tradition, known as Ṭarīqah ‘Alawīyah, while also providing new interpretations and practices of this thariqah. This article helps to enhance our understanding of the Hadrami diaspora in the Indian Ocean region, the dynamics of Sufi networks, and the roles of women in Indonesian Islam.